2013
DOI: 10.3109/02699052.2012.743184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neuroprotective therapies (hypothermia and cyclosporine a) on dopamine-induced apoptosis in human neuronal SH-SY5Y cells

Abstract: Hypothermia has a marked protective effect against apoptotic cell death induced by dopamine in a human neuroblastic cell line. The neuroprotective effect of CyA described with other apoptotic cell death stimuli was not demonstrated with our experimental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It is important to note that most evidence of the neuroprotective effects of APs has been observed when cell cultures were exposed to different types of cell damage or stress [21,36,42]. In this study, we induced neurotoxicity with high concentrations of DA and GLU as reported in other studies with neuroblastoma cell lines [21,[43][44][45][46]. GLU and DA are essential neurotransmitters, but in excess in the extracellular environment, they may induce neuronal damage and degeneration, which is involved in the pathophysiology of schizophrenia.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…It is important to note that most evidence of the neuroprotective effects of APs has been observed when cell cultures were exposed to different types of cell damage or stress [21,36,42]. In this study, we induced neurotoxicity with high concentrations of DA and GLU as reported in other studies with neuroblastoma cell lines [21,[43][44][45][46]. GLU and DA are essential neurotransmitters, but in excess in the extracellular environment, they may induce neuronal damage and degeneration, which is involved in the pathophysiology of schizophrenia.…”
Section: Discussionmentioning
confidence: 65%
“…GLU and DA are essential neurotransmitters, but in excess in the extracellular environment, they may induce neuronal damage and degeneration, which is involved in the pathophysiology of schizophrenia. Different mechanisms are involved in such neurotoxicity, including oxidative stress, oxytosis, mitochondrial damage and cellular apoptosis [13,43,45,46], which could be affected in different ways by CLZ and JNJ treatments. JNJ showed a potential neuroprotective effect in vitro, as it reduced the activation of caspase 3 induced by DA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations